WEBSITE BASED GOODS INVENTORY INFORMATION SYSTEM - Nabyla, Fuaida; Ihsani, M. Wildan; Syauqi, Achmad (STKIP Pesisir Selatan, 2023)
Inventory data management is a critical aspect that must be considered. Routine data collection processes can cause fluctuations in the volume and status of data. Therefore, traditional recording methods are now less efficient in handling the volume and complexity of these processes. It is important to not only document inventory data, but also manage it with accuracy so that it can be accessed completely without error. Thanks to technological advances, computerization has provided efficient online system-based solutions in addressing these issues. One application of this technology was carried out at the Kretek village office, which previously still relied on traditional recording methods. With the new web-based information system, village employees can manage inventory data, outgoing goods data and loans easily. This system was developed using Hypertext Preprocessor MyAdmin, with Prototype as the development approach. To ensure system performance and reliability, testing is carried out through Blackbox Testing and User Acceptance Test.